Five-Axis Printing of Continuous Fibers on the Mold - Paweł Michalec; Marius Laux; Gidugu Lakshmi Srinivas; Robert Weidner; Mathias Brandstötter (Journal of Manufacturing and Materials Processing)
This paper explores a five-axis printing method designed to improve the fabrication of continuous fiber-reinforced thermoplastic composites (CFRTPCs), essential for producing lightweight, complex structures in advanced manufacturing. Traditional CFRTPC placement techniques often face challenges with precision, scalability, and optimal fiber orientation, especially in customized, small-scale applications. The proposed five-axis printing technique overcomes these issues by enabling precise fiber orientation and the production of robust spatial structures using 3D-printed molds compatible with CFRTPCs. Validation through three-point bending and surface quality tests revealed that five-axis printed cylindrical-lattice samples, with fibers oriented at 45°, exhibited superior mechanical properties and surface quality. The five-axis printed samples achieved a load-to-weight ratio 27% higher than traditional samples and maintained their shape even under significant deformation. Surface quality improved significantly, with roughness values reduced from 37.63 µm to approximately 12 µm. This method advances CFRTPC applications in industries requiring complex, lightweight components.